DECOMPOSITION OF KAZAKHSTAN’S ECONOMIC GROWTH AND MODELING OF LABOR, CAPITAL AND TOTAL FACTOR PRODUCTIVITY CONTRIBUTIONS - S. N. Alpysbayeva; S. Zh. Shuneyev; G. V. Stroyeva (Экономика: стратегия и практика, 2019)
The study aims to decompose and model economic growth of Kazakhstan by production factors in order to justify the priorities of long-term economic policy. The latest researches made by the experts of international institutions draw the attention to high correlation between the dynamics of real GDP and total factor productivity (TFP) (WB and others). It is assumed that the contribution of the factor capital (investment) will not make a significant additional contribution to the further economic growth of Kazakhstan, which is associated with a decrease in the marginal return on capital. For a more in-depth study of this problem a review of modern theories and methodologies for calculating the contribution of production factors to economic growth was carried out. Research methods. The use of modern methodological approaches allowed to decompose Kazakhstan’s economic growth and to model the contribution of production factors and aggregate factor productivity to Kazakhstan’s economic growth. Several methods were used to assess the contribution of factors of production to the growth of Kazakhstan’s GDP: an analytical and production method, including taking into account the contribution of the factor “natural resources”. The analytical method is based on the structural model of GDP in the form of the sum of consumption of fixed capital and the number of employees. The production method is based on the Cobb-Douglas two-factor production function using the contribution of capital, labor and total factor productivity (TFP), which reflects all other implicit factors related to the conversion of capital and labor costs into manufactured products, such as technology, human capital and organizational and legal institutions. Results and conclusions of the study. The obtained results allow to develop adequate measures of macroeconomic and structural policies in order to improve the effectiveness of the fundamental factors of economic growth (labor, capital and natural resources) in the long term ensuring sustainable competitiveness of the economy of Kazakhstan.